Integration of AI GPTs in Writing Journal Article and Their Impact on Academic Writing Academy Participant’s Perception - Azra Nur Izzati Aziz; Moh. Nur Arifin; Kheryadi Kheryadi (Journal of Educational Sciences, 2026)
This study examines students' perceptions of ChatGPT use in scientific journal writing following participation in the Academic Writing Academy at UIN Banten. The growing adoption of artificial intelligence in academic settings motivated this research, given its potential to improve writing efficiency while raising ethical and pedagogical concerns. A qualitative design was employed, utilizing open-ended questionnaires distributed to 15 students from various academic departments. Data were analyzed through thematic analysis to identify recurring patterns in student perceptions. Findings indicate that students generally regard AI as beneficial for enhancing textual coherence, enriching vocabulary, and reducing time spent on academic writing. These results align with previous studies affirming AI's role in supporting writing quality. Nevertheless, participants expressed concerns over diminished originality, excessive reliance on AI-generated content, and insufficient critical evaluation of such outputs. Overall, this study confirms that AI integration in academic writing presents both opportunities and challenges. While AI holds potential to boost student productivity, its use in educational contexts must be accompanied by the development of digital literacy, critical thinking, and academic ethical awareness. Educator guidance remains essential to ensure that AI serves as a supportive tool rather than a replacement for students' creativity and originality.